2018
DOI: 10.1111/cfs.12579
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing complex trauma in child welfare‐affected mothers of colour

Abstract: Child welfare-affected mothers of colour live with the deleterious effects of complex trauma unrecognized by the child welfare system. Child welfare system instead focuses on mothers' more overt functional difficulties, facilitating a misalignment between mothers' felt needs and mandated services. Qualitative data from a mixedmethods study were used to explore the phenomenon of complex trauma in 20 urban-dwelling mothers using a combined interpretive phenomenological and directed content analysis. Mothers expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…While the focus is primarily on the trauma experienced by children allegedly by their parents, parents also are vulnerable to trauma. Losing their children, even temporarily to foster care, a traumatic event in itself (Stephens, 2019), is compounded by fears for their children's safety in such settings (Stephens et al, 2017). Allegations of maltreatment while children are in foster care are not unusual (Katz, Courtney, & Novotny, 2017; Tittle, Poertner, & Garnier, 2008).…”
Section: The Intersection Of Trauma Race and Classmentioning
confidence: 99%
“…While the focus is primarily on the trauma experienced by children allegedly by their parents, parents also are vulnerable to trauma. Losing their children, even temporarily to foster care, a traumatic event in itself (Stephens, 2019), is compounded by fears for their children's safety in such settings (Stephens et al, 2017). Allegations of maltreatment while children are in foster care are not unusual (Katz, Courtney, & Novotny, 2017; Tittle, Poertner, & Garnier, 2008).…”
Section: The Intersection Of Trauma Race and Classmentioning
confidence: 99%
“…These broad categories often overshadow the complex problems with which mothers involved with the CW system struggle (Chemtob, Griffing, Tullberg, Roberts, & Ellis, 2011), highlighting the problematic behaviors without sufficient clarification of the underlying traumatic experiences that need to be addressed. More specifically, emerging research has sought to illuminate the nuances in the relationships between substance use and trauma exposure (Blakey & Hatcher, 2013;Stephens & Aparicio, 2017), as well as mental health and revictimization IPV (Chemtob et al, 2011), emphasizing the complex trauma with which many mothers live, requiring a trauma-informed response on the part of the CW system (Stephens, 2019;Stephens et al, 2018).…”
Section: Existing Risk Factors For Cw Involvement: Substance Use Ment...mentioning
confidence: 99%
“…Early drug use may be understood as a proxy for a gap in a mother's own early protective factors which left her exposed to a host of traumas, and that drug use is only one indicator of extensive adversity. CW services that are able to connect mothers with mental health services that are capable of responding to the complex trauma evidenced by many mothers (Stephens, 2019) and that are not retraumatizing may be helpful approaches to collaborative intervention.…”
Section: Implications For Policy and Practicementioning
confidence: 99%
“…The fear of IPV, which may happen due to their partner finding out about their HIV status, increases the possibility of early mixed feeding, thereby exposing the infant to the danger of motherto-child (vertical transmission) of HIV [20,21]. Similarly, it has been confirmed that maternal exposure to IPV is associated with suboptimal breastfeeding practices [22,23] Besides their feeding practices being negatively affected by IPV, Black women are very likely to face life-threatening, lethal injuries and homicides [24,25]; have their children separated from them [26], experience social stigma [27]; be at higher risk of acquiring HIV and other sexual diseases [28]; have low confidence and self-esteem [29]; become incarcerated [26]; engage in substance abuse activities [30]; and have an increased likelihood of mother-to-child HIV transmission as a result of early mixed feeding [31].…”
Section: Introductionmentioning
confidence: 99%